Forward-looking university curricula and enterprises for renewable energies. (9th September 2021) - Ahamer, Gilbert
The new EU Commission decided on a European 'Green Deal' having ten clear targets. This case study is suggested as a possible implementation of this 'Green Deal' with a focus on Eastern Europe. This article proposes a long-term strategy for higher education on renewable energies, as is additionally in line with the EU Renewed Agenda which requires: 1) university curricula : creating new and enhancing existing university curricula on renewable energy sources (RES), energy efficiency and climate protection; 2) science-business cooperation : preparing concrete and financeable projects in the fields of RES, circular economy and climate protection in order to implement the Paris targets and the Green Deal, including their financing. This case study means founding a prospective university-business network for Western and Eastern Europe and thus promoting social transition to sustainability.